1986
DOI: 10.2105/ajph.76.5.561
|View full text |Cite
|
Sign up to set email alerts
|

Health status and access to health services among the urban homeless.

Abstract: Self-reported health status and access to care were reported for 238 homeless adults in Los Angeles. One-third reported their health as fair or poor; women reported more health problems than men. Half (53 per cent) of the sample reported no regular source of care, and most (81 per cent) were without health insurance. Lack of financial resources and health insurance were reported as important barriers to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(57 citation statements)
references
References 3 publications
5
52
0
Order By: Relevance
“…Considerable research has shown a lack of access to primary care and/or inappropriate use of health care services among general samples of homeless or unstably housed persons (Aday 2001;D'Amore, Hung et al 2001;Douglass et al 1999;Kushel et al 2001;Lim et al 2002;Robertson and Cousineau 1986). Limited or inadequate health care utilization has also been reported among unstably housed persons living with HIV (Arno et al 1996;Conover and Whetten-Goldstein 2002;Cunningham et al 2007;Douaihy et al 2005;Masson et al 2004;Pulvirenti et al 2003;Smith et al 2000;Stewart et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has shown a lack of access to primary care and/or inappropriate use of health care services among general samples of homeless or unstably housed persons (Aday 2001;D'Amore, Hung et al 2001;Douglass et al 1999;Kushel et al 2001;Lim et al 2002;Robertson and Cousineau 1986). Limited or inadequate health care utilization has also been reported among unstably housed persons living with HIV (Arno et al 1996;Conover and Whetten-Goldstein 2002;Cunningham et al 2007;Douaihy et al 2005;Masson et al 2004;Pulvirenti et al 2003;Smith et al 2000;Stewart et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…2 Numerous reports have described the health care needs of various homeless subgroups, with most addressing the health problems of adult individuals and children. [3][4][5][6][7][8][9][10][11][12] Surprisingly, the literature offers little information about the health status and service use patterns of homeless female heads of household and how their health and health care patterns compare with those of their housed counterparts. Although several descriptive reports and studies on homeless adult individuals have included female heads of household as part of the sample, 3,4,7,10 they have not reported specifically on the health needs of these women.…”
mentioning
confidence: 99%
“…In the Birmingham sample, unmet need was somewhat more common among women and persons characterized as non-Black, a finding not explained by this analysis. Several characteristics associated with unmet need were more prevalent in 2005 (and are relevant in other research 3,22,32,[35][36][37]42 ). These included older age, higher competing priority scores, higher physical symptom count, and greater proportions with some chronic diseases.…”
Section: Discussionmentioning
confidence: 81%